Mathematic Thinking Profile Of Students With High Learning Motivation - Riawan, Nova (Universitas Sebelas Maret, 2021)
This study aimed to know about high learning motivation students' in mathematical critical thinking skills. This study used a qualitative method and data collection techniques consisted of written tests and interviews. This study used triangulation techniques that compared data of test and interview data. The qualitative data analysis techniques were data collection, data presentation, and drawing conclusions. The results showed that subject critical thinking skills with high motivation are able to understand the problems in the problem and can use the information obtained appropriately to complete each step in the problem. These conditions, students can also explain what was done in the process and can get conclusions, do not forget the review that students do will help solve the problem.